2017
DOI: 10.1002/adhm.201700328
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots Downregulate Multiple Multidrug‐Resistant Genes via Interacting with Their C‐Rich Promoters

Abstract: Multidrug resistance (MDR) is the major factor in the failure of many forms of chemotherapy, mostly due to the increased efflux of anticancer drugs that mediated by ATP-binding cassette (ABC) transporters. Therefore, inhibiting ABC transporters is one of effective methods of overcoming MDR. However, high enrichment of ABC transporters in cells and their broad substrate spectra made to circumvent MDR are almost insurmountable by a single specific ABC transporter inhibitor. Here, this study demonstrates that gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…It is reported that pretreatment of cells with graphene quantum dots downregulates multidrug‐resistant genes and improves the chemotherapeutic efficiency intrinsically . However, the toxicities of GPD D and GPTD D without laser irradiation was low and a strong MDR effect was observed (Figure C).…”
Section: Methodsmentioning
confidence: 97%
“…It is reported that pretreatment of cells with graphene quantum dots downregulates multidrug‐resistant genes and improves the chemotherapeutic efficiency intrinsically . However, the toxicities of GPD D and GPTD D without laser irradiation was low and a strong MDR effect was observed (Figure C).…”
Section: Methodsmentioning
confidence: 97%
“…It is reported that pretreatment of cells with graphene quantum dots downregulates multidrug-resistant genes and improves the chemotherapeutic efficiency intrinsically. [12] However,t he toxicities of GPD D and GPTD D without laser irradiation was low and as trong MDR effect was observed ( Figure 3C). Ther easons for such different results can be different surface coatings,c oncentrations,a nd sizes of graphene derivatives as well as incubation times between our experiments and the reported work.…”
Section: Zuschriftenmentioning
confidence: 94%
“…Graphene quantum dots have exceptional physicochemical properties, good biocompatibility, low cytotoxic activity and emit intrinsic fluorescent light [53]. In addition to these properties, it was recently found [64] that a preincubation with GQDs can inhibit P-gp in MCF-7/ADR cell line-which overexpress this ABC transporter-via alternation modulation of the integrity and permeability of the cell membrane or depleting ATP pools. In addition, GQDs seems to be downregulating the P-gp (MDR1), MRP1 and BCRP genes of every cell line investigated in that study via interaction with their C-rich promoter region.…”
Section: Graphenementioning
confidence: 99%